PSXVI-4 Effects of monensin concentration in a free-choice mineral and byproduct supplementation on growth and reproductive performance of developing beef heifers. (7th December 2018) - Weiss, C; Beck, P; Kegley, E; Tucker, J; Hubbell, D
Abstract: The objective of this experiment was to compare monensin concentration in a self-fed mineral supplement (0, 882, or 1, 764 mg/kg) in combination with supplemental corn gluten feed or soybean hulls on performance and reproductive characteristics of prepubertal heifers (n = 60) in a 2 × 3 factorial arrangement. Heifers grazed 12 (2.0-ha) nontoxic endophyte-infected tall fescue ( Festuca arundinacea ) pastures (5 heifers/pasture) from 25 January to 10 May. Supplements were fed at 0.75% of body weight (BW ) prorated into 5-d/wk. Bodyweights were collected un-shrunk for 2-d at the beginning and end of the experiment (start of breeding). Prior to breeding, reproductive tract scores were determined via rectal palpation to measure the development of the uterine horns and ovarian structures. Data were analyzed as a randomized complete block design with a factorial arrangement of treatments using the MIXED procedure of SAS. Pasture was included as the experimental unit, weight block as the random term, and the model included fixed effects of monensin concentration, byproduct supplement, and monensin × byproduct interaction. Contrasts were used to test for linear and quadratic effects of monensin level, and control versus monensin treatments. Treatment means were determined using the LSMEANS statement of SAS with the PDIFF option, adjusted using the Tukey test. Mineral intake and monensin consumption were analyzed similarly, but as a repeated measure using compound symmetry as the covariance structure. No monensin × supplement interactions were detected ( P > 0.50). Neither monensin nor supplement type affected ( P ≥ 0.62) final BW, total BW gain, average daily gain, or pregnancy rates. Reproductive tract scores tended ( P = 0.10) to be improved by monensin inclusion. Although there was no effect of monensin on gain performance, the changes in reproductive tract scores may indicate improved reproductive maturity at breeding.